THE EFFECT OF DIFFERENT FOOD PRODUCTS ON MASTICATION ACTIVITY (Лучшие интеллектуальные исследования, 2025)
Abstract: Mastication is a vital physiological process that facilitates digestion by mechanically breaking down food into smaller particles. The physical and chemical properties of food significantly influence mastication activity, including chewing duration, force, and muscle activation patterns. This article reviews how various food products, differing in texture, hardness, and moisture content, affect masticatory function. Understanding these effects is essential for nutrition science, dental health, and designing food suitable for populations with chewing difficulties.